2016
DOI: 10.11648/j.ajche.20160404.11
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatography-Mass Spectrometric Analysis of Isotopic Abundance of <sup>13</sup>C, <sup>2</sup>H, and <sup>18</sup>O in Biofield Energy Treated p-tertiary Butylphenol (PTBP)

Abstract: p-tert-Butyphenol (PTBP) is a phenolic monomer used in the synthesis of numerous industrially useful chemicals.The current research work aimed to evaluate the effect of the biofield energy treatment on the isotopic abundance ratios of P M+1 /P M and P M+2 /P M in PTBP using gas chromatography -mass spectrometry (GC-MS). The sample, PTBP was distributed into two parts -one part was designated as control PTBP and another part was considered as biofield energy treated PTBP. The biofield energy treatment was achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…The relative intensity of the peak in the mass spectra is directly proportional to the relative isotopic abundance of the molecule and the isotopic abundance ratio analysis was followed the scientific literature reported [36][37][38][39] 1 H NMR multiplicities were designated as singlet (s), doublet (d), triplet (t), multiplet (m), and broad (br). …”
Section: Isotopic Abundance Ratio Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The relative intensity of the peak in the mass spectra is directly proportional to the relative isotopic abundance of the molecule and the isotopic abundance ratio analysis was followed the scientific literature reported [36][37][38][39] 1 H NMR multiplicities were designated as singlet (s), doublet (d), triplet (t), multiplet (m), and broad (br). …”
Section: Isotopic Abundance Ratio Analysismentioning
confidence: 99%
“…So, 13 + to m/z 417 in The Trivedi Effect ® Treated sample were significantly reduced compared with the control sample. Scientific literature [37][38][39]45] reported that the vibrational energy is closely related with the reduced mass (µ) of the compound and the alteration of the vibrational energy can affect the several properties like physicochemical, thermal properties of the molecule. The relation between the vibrational energy and the reduced mass (µ) for a diatomic molecule (Equation 1) is expressed as below [42,45]…”
Section: Isotopic Abundance Ratio Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The National Center of Complementary and Integrative Health (NCCIH) has been recognized and accepted Biofield Energy Healing as a Complementary and Alternative Medicine (CAM) health care approach in addition to other therapies, medicines and practices such as natural products, deep breathing, yoga, Tai Chi, Qi Gong, chiropractic/osteopathic manipulation, meditation, massage, special diets, homeopathy, progressive relaxation, guided imagery, acupressure, acupuncture, relaxation techniques, hypnotherapy, healing touch, movement therapy, pilates, rolfing structural integration, mindfulness, Ayurvedic medicine, traditional Chinese herbs and medicines, naturopathy, essential oils, aromatherapy, Reiki, cranial sacral therapy and applied prayer (as is common in all religions, like Christianity, Hinduism, Buddhism and Judaism) [19]. The Biofield Energy Treatment (The Trivedi Effect ® ) has been extensively studied with significant outcomes in many scientific fields such as cancer research [20], altered antimicrobial sensitivity of pathogenic microbes in microbiology [21][22][23], biotechnology [24,25], genetics [26,27], changing the structure of the atom in relation to the various metals, ceramics, polymers and chemicals materials science [28][29][30], altered physical and chemical properties of pharmaceuticals [31,32], nutraceuticals [33,34], organic compounds [35][36][37], and improved overall growth and yield of plants in agricultural science [38,39].…”
Section: Introductionmentioning
confidence: 99%